Budidaya Lele Dalam Ember dan Upaya Pemasaran Digital Menggunakan Media Sosial - Alya Masitha; Tri Stiyo Famuji; Adiyah Mahiruna; Rahmat Riansyah; Maulana Muhammad Jogo Samodro (Fakultas Teknik Universitas Cenderawasih, 2024)
The community service program titled 'Catfish Farming in Buckets and Digital Marketing Efforts Using Social Media' aims to provide participants with both theoretical knowledge and practical skills on simple, cost-effective, and appropriate methods for catfish farming in limited spaces. This initiative responds to the needs of the Tembalang community, which seeks to engage in farming activities on limited land while also exploring ways to market their agricultural products via social media platforms. The training was conducted using a participatory approach, which incorporated theory, hands-on practice, and interactive discussions. The content of the training included, among other things, techniques for catfish farming in buckets as well as strategies for utilizing social media to market the cultivated catfish products. Participants were guided to apply proper aquaculture practices using the provided cultivation buckets and equipment, and were then asked to capture images of their farming outcomes to be used as marketing content on social media. The implementation of this activity proceeded smoothly, and the participants showed strong enthusiasm throughout the process. It is anticipated that this training will enable the Tembalang community to effectively leverage technology, particularly social media platforms such as WhatsApp, as a tool for digital marketing of their catfish farming products.